From policy to everyday life: A multidimensional study of low-income urban housing in China - Yu, Li; University of Lethbridge. Faculty of Arts and Science (Lethbridge, Alta. : University of Lethbridge, Dept. of Geography, 2020)
This dissertation is a combination of four papers that explore the housing issues of the low-income group in urban China. The first paper uses a policy-cycle analytical framework to portray the dynamic process of national housing policy evolution from 1998 to 2017 with an emphasis on the changing role of China’s central government. The second paper examines localization processes of China’s low-income housing policy in two major cities, aiming to advance the debates over how central-local dynamics, amidst the state’s rescaling processes, have played out in China. The third paper explores housing mobility among low-income urban residents in Shanghai and Chengdu. It investigates how life-cycle factors, housing experience, place-based factors, and their interactions together shape individual moving intentions. The last paper proposes a four-period model to reconceptualize the housing career of the urban poor and depicts a vivid housing trajectory by analyzing their lived experiences in each period.
Keywords: City planning -- China; Equality -- China; Housing -- China; Housing policy -- China; Low-income housing -- China; Political geography -- China; Dissertations, Academic